Pendidikan Karakter di Universitas Pancasakti Tegal - Basukiyatno; Budiyono; Beni Habibie (Universitas Pancasakti Tegal, 2017)
The aim of this research was to describe the process and the role of character education at University of Pancasakti Tegal. The research used qualitative descriptive approach. Data collected by Penelitian menerapkan pendekatan diskriptif kualitatif. Data obtained by observation and depth interviews with a number of lecturer, staff, and student who got involved in character education at University of Pancasakti Tegal, in limited ways. The data sources were not chosen randomly, but were determined to people who were considered to know a lot about the problems studied. Data processing run simultaneously withdata collection, as well as through the process of triangulation data so that the data obtained was tested. The results of the study illustrated, that the implementation of character education at the University Pancasakti Tegal run through various units, namely units Course Personality Development, Student Activity Unit and Spirituality Unit , each had been running well, but all three units need to be synergized and continuously improved. The implication of these results is that the character education at the University Pancasakti Tegal be laid out in a comprehensive and enhanced on an ongoing basis so that the results can really helpful.